2021
DOI: 10.1002/pds.5257
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model algorithm to identify anaphylaxis in adults with type 2 diabetes inU.S.administrative claims data

Abstract: Purpose: To use medical record adjudication and predictive modeling methods to develop and validate an algorithm to identify anaphylaxis among adults with type 2 diabetes (T2D) in administrative claims.Methods: A conventional screening algorithm that prioritized sensitivity to identify potential anaphylaxis cases was developed and consisted of diagnosis codes for anaphylaxis or relevant signs and symptoms. This algorithm was applied to adults with T2D in the HealthCore Integrated Research Database (HIRD) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Censoring events included disenrollment from the health care system, discontinuation of the index drug (no prescription refill for >30 days after the end of the last prescription’s supply), switch to another GLP-1 RA (lixisenatide and insulin glargine/lixisenatide FRC were considered to be the same treatment, as were liraglutide and insulin degludec/liraglutide FRC), death, or end of the study period. This study was also purposed to develop and validate an algorithm to identify anaphylaxis cases in the setting of an administrative claims database ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Censoring events included disenrollment from the health care system, discontinuation of the index drug (no prescription refill for >30 days after the end of the last prescription’s supply), switch to another GLP-1 RA (lixisenatide and insulin glargine/lixisenatide FRC were considered to be the same treatment, as were liraglutide and insulin degludec/liraglutide FRC), death, or end of the study period. This study was also purposed to develop and validate an algorithm to identify anaphylaxis cases in the setting of an administrative claims database ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study outcome was the first anaphylaxis event identified using a predictive model algorithm developed as the initial stage of this study ( 8 ). The algorithm was based on ICD-9-CM and ICD-10-CM diagnosis codes, Current Procedural Terminology and Healthcare Common Procedure Coding System procedure codes, and National Drug Code and General Product Identifier medication codes.…”
Section: Methodsmentioning
confidence: 99%
“…By excluding noncases using conditional sampling, however, it may be possible to target a sample that is enriched in people more likely to be cases 24 . For instance, one could design a “screening” algorithm aimed at capturing all (or nearly all) of the cases so that it has near‐perfect sensitivity, while still being specific enough to exclude many noncases 25 . Validating a random sample of people identified by such as screening algorithm could generate sufficient cases to be used to estimate sensitivity of algorithms designed to have high PPVs (Table 1).…”
Section: Validation To Inform Quantitative Bias Analysismentioning
confidence: 99%
“…To date, most attempts to accurately identify anaphylaxis events using automated algorithms applied to structured medical claims data have had limited success ( 20 ). This is in part due to the challenges of diagnosing a condition with diverse clinical presentation ( 19 ), reliance on structured medical claims data ( 21 , 22 ), and the practice of “rule-out” coding ( 23 ). An algorithm published by Walsh et al in 2013 ( 22 ) intended to improve identification of anaphylaxis in FDA safety surveillance studies using structured diagnosis, procedure, and encounter data.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Ball et al ( 34 ) and Yu et al ( 35 ) have found that information extracted from EHRs about exposures, comorbidities, presenting symptoms, treatments, and disease severity appearing in chart notes may be useful for identifying actual anaphylaxis. Recent studies have used natural language processing (NLP) and machine-learning methods to improve the identification of anaphylaxis events but did not include external populations to validate their findings ( 21 , 36 ).…”
Section: Abbreviationsmentioning
confidence: 99%